Static and dynamic analysis of marine pipelines and risers - Shanks, J. M. (Cranfield University, 1985)
This thesis investigates two slender body problems, namely the static and dynamic analysis of submarine pipeline spans and the dynamic analysis of marine risers. In view of structural and environmental similarities, these problems are closely related and where possible common analysis procedures have been developed. For the problem of pipe spanning, attention is focused on the possibility of vortex induced vibration and the associated question of span assessment. This situation arises when following the discovery of a span, an assess- ment is required to determine if any remedial repair work required. To assist in this assessment, and also to provide a more fundamental understanding of span behaviour, number of mathematical models are developed. First linear beam-column theory is used to determine the span natural frequencies and buckling load for a single span supported continuously on either side by an elastic foundation. The effects of internal/external pressures and product temperature are included and the results presented terms of two independent nondimensional parameters. Next the effects of pipe/soil friction and change in geometry are considered utilising a nonlinear Finite Element model. Theories are developed for a nonlinear pipe element with axial/bending coupling and a nonlinear nonconservative pipe/soil friction element. The effects of initial seabed geometry and finite amplitude vibration are included and it shown that span frequencies are sensitive to both end friction constraints and seabed geometry. . For marine riser dynamics, an attempt is made to synthesise the best parts from the many and varied analysis methods developed to date, into a simple but flexible design-orientated program. The riser is represented using a Finite Element model similar to that employed for the pipeline spans, and a reduced set of equations obtained using a component mode synthesis method. Several riser/ articulated column designs are considered and the results found to agree with published data.